2015
DOI: 10.3390/nu7095370
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptance of Population-Level Intervention Strategies for Healthy Food Choices: The Role of Perceived Effectiveness and Perceived Fairness

Abstract: The present study investigates acceptance of intervention strategies for low-calorie snack choices that vary regarding the effect they have on consumers’ freedom of choice (providing information, guiding choice through (dis)incentives, and restricting choice). We examine the mediating effects of perceived effectiveness and perceived fairness, and the moderating effects of barriers to choose low-calorie snacks and perceived responsibility for food choice. Data was collected through an online survey, involving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
58
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 43 publications
(71 reference statements)
8
58
1
Order By: Relevance
“…Further recommendations of relevance may be drawn from parallel literature in neighbouring fields such as health including, for example, discussion of the perceived effectiveness and acceptability of taxes on alcohol and sugared products [73][74][75].…”
Section: Recommendations To Improve the Public Acceptability Of A Meamentioning
confidence: 99%
“…Further recommendations of relevance may be drawn from parallel literature in neighbouring fields such as health including, for example, discussion of the perceived effectiveness and acceptability of taxes on alcohol and sugared products [73][74][75].…”
Section: Recommendations To Improve the Public Acceptability Of A Meamentioning
confidence: 99%
“…The perceived fairness, on the other hand, refers to the extent to which people perceive interventions to be a fair way of stimulating healthy food choices. Bos et al (2015a) conclude that across different levels of intrusiveness perceptions of personal and societal effectiveness only differ marginally. When looking at the perceived fairness, however, the more intrusive interventions become, the less they are perceived as fair.…”
mentioning
confidence: 81%
“…Additionally, all the products were priced €0.75, which is similar to the selling prices of other vending machines on the university campus. The interventions used in the experimental conditions were chosen based on earlier research by Bos et al (2015a), where they were identified as less accepted interventions within their intervention type.…”
Section: Assortment In Vending Machinementioning
confidence: 99%
See 2 more Smart Citations